Contractors' perspective on construction waste minimisation : strategies and barriers / Nik Nurul Salsabila Hasan Nualdin and Norazlin Mat Salleh - Hasan Nualdin, Nik Nurul Salsabila; Mat Salleh, Norazlin (2019)
Higher demand in construction sectors in Malaysia has contributed the increasing of construction material waste which causes environmental concerns by bringing them for final disposal in landfills. The limited numbers of landfill to handle the increased generated waste by construction parties increase illegal dumping sites. Practicing waste minimization is the most desirable method in waste management hierarchy that can be useful in reducing the possibility of removal of waste from landfill. Thus, the aim of this research is to assess contractors' perspectives towards waste minimization by the extent to which waste minimization strategies are adopted and the barriers faced in minimizing construction waste. A total of 115 Questionnaires were distributed to building contractors in Kelantan and 46 completed questionnaires were analyzed using the Statistical Package for Social Science (SPSS). The result indicated that 'Monitoring laborer's attitudes, 'Ensuring the compliance of the waste management plan' and 'site management' are perceived as the three most important strategies adopted by contractor. Furthermore, lack of financial incentives become the most important barriers faced by contractor in minimizing construction waste. From this study, useful information concerning strategies and barrier to waste minimization from the perspectives of contractor are obtained.